PELAKSANAAN MALAKOK SUKU TERHADAP ORANG DILUAR SUKU MINANG YANG AKAN MENIKAH DENGAN ORANG SUKU MINANG ASLI DI NAGARI KURANJI KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia recognizes the existence of customary law communities, namely, in Article 18 B of the 1945 Constitution which states that the State recognizes and respects indigenous peoples and their traditional rights as long as they are still alive and in accordance with the development of the nation, society and principles. The Unitary State of the Republic of Indonesia as regulated in Law.Marriage according to the Minangkabau customary culture is one of the important events in the life cycle and is a very meaningful transitional period in forming a small group of new family successors. Problems often arise if newcomers do not practice the Malakok Custom in Nagari Kuranji either before marriage or those who have married but have not yet practiced the Malakok custom.The Malakok is a process of integration (integration) of newcomers into the original pesukuan structure, as well as the agreement of the nagari to form a new tribe for newcomers. Malakok is commonly referred to as Minangkabau-style assimilation. All of these newcomers were also called nephews, although they had different rights from the original nephews of the tribe. In the Malakok Adat there are several stages, firstly pre-implementation, secondly during the Malakok period, third after Malakok and the fourth is the rights and obligations of the parties after the Malakok tribe.Keyword: Wedding, Malakok Custom.